Psychological characteristics factor of success in karate athletes - Kostovski, Z.; Aleksovska, V. L.; Iber, A. (Sports Science and Health, 2019)
A survey was conducted with two sub-samples of respondents, karate athletes representatives (members of the national team) and karate athletes competitors in the kumite (sports fight). The survey was conducted on a stratified sample of 32 respondents divided into two groups, 16 karate representatives and 16 karate competitors, males, seniors from the Republic of Macedonia. The main purpose of the research is to determine the differences in the psychological characteristics between the two sub-samples of the respondents. In the research, a total of 13 variables for the assessment of psychological characteristics were applied: for estimation of emotional characteristics six (6) variables, three (3) variables for assessment of the motivational dispositions, for assessment of the specific intellectual characteristics (3) three variables and one variable for assessing the general intellectual characteristic. The basic statistical parameters are determined using the basic descriptive statistics for the two groups of respondents separately, while for determining the differences in the arithmetic means of the psychological characteristics, a T-test for small independent samples was applied. From the analysis of the data from the basic descriptive statistical parameters, it was established that in all applied variables, homogeneity of the results as well as normal distribution was obtained, with very small deviations present in two variables. The results of the T - test obtained in the survey show statistically significant differences in the entire analyzed space between the two groups, with the exception of two variables (L - social desire and P - psychoticism), i.e. differences were found in 11 variables from a total of 13 examined variables.